Letter - Roberts, Wilfrid
001-0065-001 National Joint Committee for Spanish Relief AND BASQUE CHILDREN'S TRUST LTD. President: THE DUCHESS OF ATHOLL D.B.E. D.C.L. Chairman: MISS ELEANOR RATHBONE. M.P Vice-chairman: THE EARL OF LISTOWEL Hon. SECRETARIES: LADY LAYTON. MR. D. R GRENFELL. M.P. MR. WILFRID ROBERTS. M.P. Hon. Treasurer: VISCOUNT CECIL OF CHELWOOD. PC. K.C. Hon. Appeals Secretary MRS. V. E. MILLER Secretary: MISS M PICKEN. 39, VICTORIA STREET. LONDON. S.W.1 Telephone ABBEY 7463 August 21st, 1945. Dear Mr. Tew son, The signatories of the enclosed (six copies) of an Appeal for Spanish Republicans in France, ask if you would add your name ? The appeal will then be sent to the News Chronicle, Times, Manchester Guardian, Herald, New Statesman & Nation, and to the big Trades Unions, as well as to a certain number of private individuals known to be sympathetic to the Spanish Cause. It would be a very great help if you would very kindly inform us whom we could contact to obtain up to date addresses of the organisations in the Trades Union Council; during the war years our records have become somewhat out of date. Yours very truly, [Wilfrid] Secretary. H. V. Tewson, Esq., Transport House, Smith Square, S.W.I 292/946/1/65